2008
DOI: 10.1039/b712970j
|View full text |Cite
|
Sign up to set email alerts
|

An improved sensitivity non-enzymatic glucose sensor based on a CuO nanowire modified Cu electrode

Abstract: CuO nanowires have been prepared and applied for the fabrication of glucose sensors with highly enhanced sensitivity. Cu(OH)(2) nanowires were initially synthesised by a simple and fast procedure, CuO nanowires were then formed simply by removing the water through heat treatment. The structures and morphologies of Cu(OH)(2) and CuO nanowires were characterised by X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, and transmission electron microscopy. The direct electrocatalytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
235
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 464 publications
(244 citation statements)
references
References 44 publications
(88 reference statements)
7
235
1
1
Order By: Relevance
“…17,18 Successful synthesis strategies have been employed to control the morphology of CuO nanostructures as nanowires, hierarchical CuO micro-/nanostructures has been studied for the extension of its sensing applications. 12,19,25 Sun et al, 18a reported the fabrication of hierarchical CuO nanoribbons using a green water/ethanol solution-phase hydrolysis of Cu x (OH) 2xÀ2 (SO 4 ) precursors. Such nanoporous CuO ribbons show a high sensitivity, low detection limit, and a good selectivity towards glucose.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Successful synthesis strategies have been employed to control the morphology of CuO nanostructures as nanowires, hierarchical CuO micro-/nanostructures has been studied for the extension of its sensing applications. 12,19,25 Sun et al, 18a reported the fabrication of hierarchical CuO nanoribbons using a green water/ethanol solution-phase hydrolysis of Cu x (OH) 2xÀ2 (SO 4 ) precursors. Such nanoporous CuO ribbons show a high sensitivity, low detection limit, and a good selectivity towards glucose.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the development of electrochemical glucose sensor and biosensor has attracted extensive attention [1][2][3][4][5][6][7][8][9][10][11]. Aiming at the construction of glucose biosensors, glucose oxidase has been widely employed due to its high selectivity and sensitivity to glucose.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considerable attention has been paid to develop non-enzymatic sensors to overcome these problems. Noble metals [5] and metal oxide nanoparticles [2,4,11] have been extensively employed to construct non-enzymatic glucose sensors. However, these sensors suffer from low selectivity, high cost and surface fouling, which greatly limit their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…High-resolution TEM indicates the nanoporous character of the nanothorn surface with a pore size (diameter) of 2-6 nm, expected to enhance the surface area of the nanothorns. It is worth noting that in an alkaline electrolytic solution, the glucose oxidation occurs in the potential range of 0.40 to 0.8 V vs. Ag|AgCl|KCl sat , where the oxidation wave for Cu(II)/Cu(III) is reported [84][85][86][87]. It was experimentally shown (pH 13.3) that the redox reaction associated with the couple Cu(III)/Cu(II) is a quasi-reversible process with one electron transferred and the determined formal electrode potential is 0.37 V vs. SCE [88,89], that is about 0.41 V vs. Ag|AgCl|KCl sat .…”
Section: Platinum and Gold-free Electrodes: Earth-abundant Transitionmentioning
confidence: 99%